2019
DOI: 10.17816/ov2019241-46
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-dependent tonometry in improving diagnostics and treatment of patients with open angle glaucoma

Abstract: Monitoring intraocular pressure in patients with open-angle glaucoma at different stages of the deve­lopment of the disease using self-measurement by a portable Icare® HOME tonometer. In study, patients were divided into 3 groups depending on the treatment prescribed. With the help of near-day monitoring, hidden IOP elevations that are not recorded during a single IOP measurement on an outpatient appointment with a doctor were detected. Perspective possibilities of prescribing drugs and regulating the mode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Nonadherence is common in glaucoma patients; nonadherence rates in these patients range from 5% to 80%. 6 Patient adherence to therapy can be improved by putting them in charge of their glaucoma care and providing them with the means for accurate self-measurements, as demonstrated by Astakhov et al 13 for the iCare ® Home tonometer (iCare Finland Oy, Vantaa, Finland). Furthermore, a study assessing the impact of self-tonometry on clinical treatment decisions demonstrated that higher IOP values detected via the iCare ® Home tonometer led to intensification of medical glaucoma treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonadherence is common in glaucoma patients; nonadherence rates in these patients range from 5% to 80%. 6 Patient adherence to therapy can be improved by putting them in charge of their glaucoma care and providing them with the means for accurate self-measurements, as demonstrated by Astakhov et al 13 for the iCare ® Home tonometer (iCare Finland Oy, Vantaa, Finland). Furthermore, a study assessing the impact of self-tonometry on clinical treatment decisions demonstrated that higher IOP values detected via the iCare ® Home tonometer led to intensification of medical glaucoma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Nonadherence is common in glaucoma patients; nonadherence rates in these patients range from 5% to 80%. 6 Patient adherence to therapy can be improved by putting them in charge of their glaucoma care and providing them with the means for accurate self-measurements, as demonstrated by Astakhov et al 13 for the iCare ® Home tonometer journals.sagepub.com/home/oed 5…”
Section: Discussionmentioning
confidence: 99%